1473 Urology Consent Forms at a District General Hospital – a Quality Improvement Project. (12th October 2021) - Bernstein, D; West, A; Preston, E; Premakumaran, P; Suleyman, N; Undre, S
Abstract: Aim: Consent is a core component of interaction between patients and healthcare professionals. Prior to surgery, forms are completed to record patient consent. As well as containing risks and benefits of the procedure, the consent form, as per guidelines 1, 2, must be legible and suitable to a patient's capacity. To evaluate compliance with local and national guidelines, a quality improvement project was undertaken at a district general hospital. Method: Over a three-week period 30 urology consent forms were selected to assess adherence to local and national guidelines. The appropriateness of consent form, patient signature, legibility, acronym use and whether the patient was offered a carbon copy were assessed. After initial data collection, all urology staff consenting patients were notified of the findings and how best to improve guideline adherence. A further three-week data collection was undertaken, though the sample set was small due to Coronavirus and Christmas. Results: The results confirmed that patients had appropriate consent forms filled out and were signed appropriately. After intervention, there was clear improvement in legibility, with no low legibility consent forms, and 100% vs 83% high or moderate legibility between data sets. Intervention also resulted in significant reduction of acronym use; 33% vs 60%. More patients were also offered to retain a carbon copy; 89% vs 40%. Conclusions: Through this intervention of highlighting local and national guidance as compared to current practice, compliance drastically improved. As the pandemic subsides, we hope regular emails to surgical teams will improve consent form completion to better patient care.